Direct and in situ examination of Li + transport kinetics in an isotope-labeled solid–electrolyte interphase - Xiaofei Yu; Stefany Angarita-Gomez; Yaobin Xu; Peiyuan Gao; Jun-Gang Wang; Xin Zhang; Minyung Song; Hao Jia; Wu Xu; Xiaolin Li; Hsin-Mei Kao; Yingge Du; et al. (Proceedings of the National Academy of Sciences, 2025)
Solid–electrolyte interphase (SEI) is the critical component in all advanced battery chemistries, whose ionic transport and electron leakage behaviors remain least understood among all battery components. Here, using unique in situ liquid secondary ion mass spectroscopy on isotope-labeled SEI, assisted by cryogenic transmission electron microscopy and constrained ab initio molecular dynamics simulation, we answer the question regarding the Li + transport mechanism across SEI and quantitatively determine the Li + mobility therein. We unequivocally unveil that Li + transport in SEI mainly follows a mechanism of successive displacement. We further reveal that in accordance with the spatial dependence of SEI structure across the thickness, the apparent Li + self-diffusivity continuously drops from the SEI–electrolyte side to the SEI–electrode side (6.7 × 10 −19 m 2 /s to 1.0 × 10 −20 m 2 /s), setting a quantitative gauging of both ionic transport behavior of the SEI layer against the underlying electrode and the rate-limiting step of battery operation. This direct study on Li + kinetics in SEI fills part of the decade-long knowledge gap about the most important component in advanced batteries and provides more precise guidelines for the tailoring of interphasial chemistries for future battery chemistries.